Adaptasi Fisiologis Bayi Baru Lahir melalui Persalinan Normal dengan Lotus Birth dan Tanpa Lotus Birth - Susi Sastika Sumi; Wa Mina La Isa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the differences in the physiological adaptation of newborns through expected delivery with lotus birth and without lotus birth at Kandai Public Health Center, Kendari City. The method used is quantitative research using a comparative study with a cross-sectional approach. The results showed differences in physiological adaptation (heart rate, respiratory rate, thermoregulated frequency, or body temperature) of newborns through expected delivery with lotus birth and without lotus birth. Respondent statistical data obtained from each physiological system of newborns showed a p-value of 0.013. In conclusion, there are differences in the physiological adaptation of newborns through expected delivery with lotus birth and without lotus birth at the Kandai Public Health Center, Kendari City. Keywords: Physiological Adaptation, Newborn, Lotus Birth, Without Lotus Birth